Victims, villains or organized community? : discrimination, social exclusion and empowerment in the media representation of urban poverty : case of barrio “El 70” in Venezuelan newspapers - Kivimäki, Johanna (2012)
The purpose of this thesis is to study the media representation of urban poverty in a developing country context, focusing specifically on the connections between media representation and social exclusion. The theoretical-methodological basis of this work draws from critical cultural studies and sociological media research, specifically from the theoretical assumptions of critical discourse analysis about media representation. The premise is the constructionist view that the media does not directly reflect the reality of urban poverty, but constructs journalist reproductions of it from a particular perspective and in a certain social context. Media representation of the subordinated groups is related to the prevailing power relations and inequalities in society. The intention is to consider whether the discrimination and exclusion experienced by the urban poor is reproduced in media representations.